The new carbohydrate intake recommendations - Jeukendrup, A. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
Carbohydrate intake during prolonged exercise has been shown to increase endurance capacity and improve performance. Until recently, the advice was to ingest 30-60 g of carbohydrate per hour. The upper limit was based on studies that demonstrated that intakes greater than 60-70 g/h would not result in greater exogenous carbohydrate oxidation rates. The lower limit was an estimated guess of the minimum amount of carbohydrate required for ergogenic effects. In addition, the advice was independent of the type, the duration or the intensity of the activity as well as the level of athlete. Since 2004, significant advances in the understanding of the effects of carbohydrate intake during exercise have made it possible to be much more prescriptive and individual with the advice. Studies revealed that oxidation rates can reach much higher values (up to 105 g/h) when multiple transportable carbohydrates are ingested (i.e. glucose:fructose). It has also been observed that carbohydrate ingested during shorter higher intensity exercise (1 h, 80%VO2max) can improve performance, although mechanisms are distinctly different. These findings resulted in new recommendations that are dependent on the duration and intensity of exercise and not only specify the quantity of carbohydrate to be ingested but also the type.